(untitled) (Agro Productividad, 2021)
Objective: To conduct a bibliographic review of the inventory and distribution of the buffalo herd, leading dairy buffalo breeds, and to map the main research topics for dairy buffaloes, emphasizing feeding methods and their effects on milk and mozzarella cheese quality. Design/Methodology/Approach: Analysis of the main research topics on dairy buffalo, through a wide review of specialized journals. Results: The production and processing of buffalo milk has gained relevance in recent years along different latitudes thanks to its nutritional qualities and the international regard for products such as mozzarella cheese. The main studies are carried out in Asia, Italy, and Brazil, emphasizing that diets are a determining factor in yield and quality of milk and its derivatives, but that genetics, environment, and animal management are what in the end model these characteristics. Study Limitations/Implications: To conduct further research on dairy buffalo, especially in Mexico, where it has important development opportunities. Findings/Conclusions: The bibliographic body of work presents practical restrictions, advances are recognized, and also the need to further research topics such as reproduction and animal welfare, management and valuation of buffalo milk and its derivatives, with the opportunity to explore organic production.